Breed and age effects on concentration of adiponectin and reproductive performance in Anglo Nubian, Etawah grade and its crossbred bucks - HAFIZUDDIN Hafizuddin; NI WAYAN KURNIANI KARJA; LISA PRAHARANI; MOHAMAD AGUS SETIADI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hafizuddin, Karja NWK, Praharani L, Setiadi MA. 2021. Breed and age effects on concentration of adiponectin and reproductive performance in Anglo Nubian, Etawah grade and its crossbred bucks. Biodiversitas 22: 1112-1119. The purpose of this study was to evaluate the effect of differences in breed and age on reproductive performance and adiponectin and testosterone production in Anglo Nubian, Etawah grade, and crossbred (Anpera) bucks. A total of 12 bucks with four individuals of each breed were used. This study collected five data points from each buck regarding adiponectin, testosterone, and reproductive performance (libido and semen characteristics). Data were analyzed with factorial analysis of variance and Duncan's test. The result shows that adiponectin concentration between breeds was significantly different (P <0.01). There were also significant differences (P<0.05) in adiponectin concentrations based on buck age. There were also significant interactions with adiponectin concentrations (P <0.01). Furthermore, testosterone concentrations showed significant differences based on breed (P <0.05) and age (P <0.05). There were also significant age-breed interactions affecting testosterone concentrations (P <0.01). Libido and semen characteristics had no significant differences based on breed and age group, and no significant age-breed interactions (P> 0.05). The heterosis effect on adiponectin concentration (48.05%), testosterone concentration (27.68%), libido (-0.61%), semen volume (-1.93%), sperm motility (0.49%), sperm normal morphology (0.18%), and sperm concentration (0.00%) was measured. In conclusion, there is a significant effect of breed, age, and age-breed interactions on the concentration of adiponectin and testosterone in bucks, and both of these variables have a high heterosis effect on crossbred bucks.